Sensitivity analysis of flood frequency on choice of data threshold limit - Saeid Eslamian; Yaser Sabzevari; Elnaz Farizi (Results in Engineering, 2025)
This study investigates the sensitivity of flood frequency analysis results to the selection of threshold limits in the partial duration series (PDS) model, using 15 hydrometric stations in Iran's Karkheh basin with 63 years of discharge records. The PDS thresholds were varied from N (record years) up to 6 N and compared to the annual maximum series (AMS) approach across return periods from 10 to 200 years. Frequency analyses were conducted using the FREQ software and multiple statistical distributions. Results revealed that increasing the number of partial values generally reduces estimated discharges, particularly at Pol Chehr, Noorabad, Pol Zal, Baba Qasem, Jologir, and Helilan stations, across all return periods. In contrast, Tang Siab and Canal Wasileh stations displayed non-monotonic trends beyond the 20-year return period. The study concludes that threshold selection significantly impacts flood quantile estimations, particularly for regions with diverse topography and catchment sizes.